2016
DOI: 10.18801/jstei.030216.21
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, biochemical indices and antioxidant activity of Peppermint (Mentha piperita L.) and Basil (Ocimum basilicum L.) in condition of hydroponics

Abstract: Dry raw material of both peppermint and sweet basil grown with the application of different hydroponic methods (cylindrical, gully, continuous, classical) exceeds soil culture 1.2-2.7 and 1.8-2.7 times. At the same time a high output (1.6-3.1 times) of secondary origin bioactive substances was observed in cylindrical and classical hydroponics systems due to the high productivity of peppermint and in the case of basil in cylindrical hydroponics system (1.2-2.9 times). For determining antioxidant activity from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Whereas the tannin compound determined higher (198.49 mg TAE /100g) under hydroponics growing condition. Similar results have also been reported in peppermint by Mairapetyan et al (2016) and Surendran et al (2017) recorded in Mentha spicata L. that's yield, organic acid concentration, and antioxidant content were higher in hydroponically grown plants. The results in Table 3 revealed that's the phytochemical quality attributes in sweet basil, which is tannin and flavonoid recorded 2 times higher (301.10 mg TAE/100g, 19.00 mg QE/g, respectively) under soilless growing condition as compared to other growing conditions.…”
Section: Resultssupporting
confidence: 88%
“…Whereas the tannin compound determined higher (198.49 mg TAE /100g) under hydroponics growing condition. Similar results have also been reported in peppermint by Mairapetyan et al (2016) and Surendran et al (2017) recorded in Mentha spicata L. that's yield, organic acid concentration, and antioxidant content were higher in hydroponically grown plants. The results in Table 3 revealed that's the phytochemical quality attributes in sweet basil, which is tannin and flavonoid recorded 2 times higher (301.10 mg TAE/100g, 19.00 mg QE/g, respectively) under soilless growing condition as compared to other growing conditions.…”
Section: Resultssupporting
confidence: 88%
“…Besides menthol, it consists of menthone, menthyl acetate, carvone, linalool, limonene, pinene and others [ 42 , 43 ]. Mentha piperita L. is an antioxidant, antimicrobial, anti-allergic, antispasmodic, anticarcinogenic and antiviral herb [ 44 , 45 , 46 , 47 , 48 , 49 ]. These properties have ensured its wide application in various industries, including medicine, cosmetics and the food industry [ 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of sweet basil, however, the difference is insignificant. In both situations, however, lipid free radical oxidation pathways were suppressed Stepan 4) . By integrating IoT and a mobile phone to automatically operate and monitor an automatic hydroponics vegetable system, users who need to plant hydroponic vegetables would gain ease and productivity.…”
Section: Research Backgroundmentioning
confidence: 96%